2022
DOI: 10.26434/chemrxiv-2022-rkm8l-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interplay of static and dynamic disorder in the mixed-metal chalcohalide Sn₂SbS₂I₃

Abstract: Chalcohalide mixed-anion crystals have seen a rise in interest as ‘perovskite-inspired materials’ with the goal of combining the ambient stability of metal chalcogenides with the exceptional optoelectronic performance of metal halides. Sn₂SbS₂I₃is a promising candidate, having achieved a photovoltaic power conversion efficiency above 4%. However, there is uncertainty over the crystal structure and physical properties of this crystal family. Using a first-principles cluster expansion approach, we predict a diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The observed inhomogeneous broadening is consistent with the presence of significant structural disorder, giving support to recent crystallographic models of Sn 2 SbS 2 I 3 which exhibit multiple S and I positions as well as Sn and Sb site mixing. 21 Moving down to the heavier pnictide (Pn), the crystal structure of Sn 2 BiS 2 I 3 shows two unique Sn sites, one of which exhibits mixed Pn occupancy (50% Sn:50% Bi). Similar 119 Sn NMR line widths were observed for Sn 2 SbS 2 I 3 and Sn 2 BiS 2 I 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The observed inhomogeneous broadening is consistent with the presence of significant structural disorder, giving support to recent crystallographic models of Sn 2 SbS 2 I 3 which exhibit multiple S and I positions as well as Sn and Sb site mixing. 21 Moving down to the heavier pnictide (Pn), the crystal structure of Sn 2 BiS 2 I 3 shows two unique Sn sites, one of which exhibits mixed Pn occupancy (50% Sn:50% Bi). Similar 119 Sn NMR line widths were observed for Sn 2 SbS 2 I 3 and Sn 2 BiS 2 I 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…80 In addition, we also included in our search the DCGAT-3 data set by Schmidt et al, which was used to train their thirdgeneration crystal-graph attention network and includes about 3.18 million crystalline compounds, including a large number of quaternary materials. Nicolson et al, 17 which provides us with an opportunity to validate our computational approach. Our PBEsol results for the energy differences between the Cmc2 1 and P2 1 /c phases and the Cmcm phase are reported in Table 1 and are in good agreement with the optB86b-vdW results of Kavanagh and Nicolson.…”
Section: Novelty Checkmentioning
confidence: 96%
“…16,18−22 changes to a monoclinic P2 1 /c structure below 100 K. 21 This P2 1 /c structure was then shown to be lower in energy than the Cmcm and Cmc2 1 phases for Sn 2 SbS 2 I 3 by DFT. 17 In addition, for Sn 2 SbS 2 I 3 , UV−vis absorption spectroscopy and DFT calculations revealed that the optical band gap lies below 1.5 eV. 11,12,23 This limits its applications to single-junction solar cells as the band gap is close to the optimum value of harvesting solar radiation (1.3 eV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Among them, chalcohalide PIMs have emerged as promising materials having an ns 2 electronic configuration as well as a cation−halide combination. 11,13,14 Recently, Nie et al 13 have synthesized a solar cell based on tin−antimony sulfoiodide (Sn 2 SbS 2 I 3 ) using a single-step, solution-based chemical deposition process, exhibiting a power conversion efficiency (PCE) of 4.04%. They have also demonstrated its stability against air, moisture, and light illumination.…”
mentioning
confidence: 99%